Exploring the Influence of Entrepreneurial Knowledge and Self-Confidence on Students' Entrepreneurial Interest: A Mixed-Methods Study - Kurniawan, Dedi; Koswara, Dayat (Cebong Journal, 2024)
This research investigates the influence of entrepreneurial knowledge and self-confidence on students' entrepreneurial interest, aiming to deepen our understanding of the factors shaping entrepreneurial aspirations among the student population. Drawing on theoretical frameworks from social cognitive theory, theory of planned behavior, and human capital theory, the study examines the relationships between entrepreneurial knowledge, self-confidence, and entrepreneurial interest through a mixed-methods approach. Quantitative data is collected through surveys administered to undergraduate and graduate students across various educational disciplines, supplemented by qualitative insights from semi-structured interviews. The analysis reveals significant positive associations between entrepreneurial knowledge, self-confidence, and entrepreneurial interest, highlighting the importance of entrepreneurship education and self-belief in fostering students' entrepreneurial aspirations. The findings underscore the need for educational institutions to integrate entrepreneurship education into curricula, provide experiential learning opportunities, and foster supportive learning environments to cultivate students' entrepreneurial talents and ambitions. Moreover, the study highlights the critical role of self-confidence in empowering students to pursue entrepreneurial ventures with confidence and resilience. Overall, this research contributes to the existing body of knowledge on entrepreneurship education and psychological factors influencing entrepreneurial behavior, providing valuable insights for policymakers, educators, and program administrators seeking to foster a culture of innovation and entrepreneurship among students.